Metal Hypersensitivity in Patients With Failure of Joint Prosthesis Treatment - Bruna, Jana; Prochazkova, Jarmila; Podzimek, Stepan; Himmlova, Lucie; Janatova, Tatjana; Vinsu, Alex (Journal of immunology research, 2025)
The objective of this study is to measure lymphocyte responses to metal antigens using MELISA (memory lymphocyte immunostimulation assay) test-modified lymphocyte transformation test (mLTT) and to evaluate metal sensitization in patients with and without the need of prosthetic surgery. This study is a case-control retrospective survey. We retrospectively analyzed all patients from 2013 to 2018 who were referred to the Institute of Dental Medicine, General University Hospital in Prague, and First Faculty of Medicine, Charles University, Prague, either following joint prosthesis-related complications or as a preoperative evaluation concerning metal hypersensitivity. For the control group, we selected healthy adults from our database. A group of 127 patients aged 25-81 years was chosen, 92 of which were female and 35 were male. The patients completed a special questionnaire aimed at information regarding their health status and history of metal exposure. After clinical examination, their peripheral blood samples were taken to perform mLTT. mLTT provided quantitative lymphocyte proliferation measurement, where a stimulation index of >2 indicated metal sensitivity. For statistical analysis, the Fisher's exact test, χ2 test, McNemar's exact test Student's paired t-test were used. By comparison of the study group and control group mLTT results, it can be stated that patients of the study group showed a higher level of lymphocyte reactivity to most of the tested metal antigens (Ag [silver], Cu [copper], Fe [iron], Mo [molybdenum], Pd [palladium], Pt [platinum], Ti [titanium], and Zn [zinc]) and an elevated incidence of metal hypersensitivity to Hg (mercury), Al (aluminum), Au (gold), Co (cobalt), Cr (chromium), Ni (nickel), and Sn (tin). The evaluation of the data obtained from patients in this study confirmed a significant clinical benefit of mLTT in diagnostics of metal hypersensitivity. Our study has revealed that the patients with the need of prosthetic surgery exhibited an elevated lymphocyte response to metal antigens. This result supports a metal-specific adaptive immune response and suggests involvement of metal exposure as a trigger for their health problems. This knowledge could be helpful in effectively enhancing the treatment of patients with need of orthopedic joint prosthesis.
Keywords: dospělí; Female; lymfocyty; Adult; ženské pohlaví; modified lymphocyte transformation test (mLTT); Metals; Lymphocyte Activation; alergie; aktivace lymfocytů; lidé; arthroplasty; studie případů a kontrol; kovy; Aged, 80 and over; retrospektivní studie; Hypersensitivity; metal; selhání protézy; Male; Case-Control Studies; Aged; lymphocyte; Lymphocytes; Joint Prosthesis; lidé středního věku; protézy kloubů; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; hypersensitivity; Prosthesis Failure; Humans